Psychoeducation on Mental Health and Psychological Well-Being of Students and Teachers at SMAS Santu Klaus Werang, West Manggarai District - Nur Dafiq; Demang, Fransiska Yuniati; Dewi, Claudia Fariday; Iwa, Kornelia Romana; Momang, Hendrianus Dwianot (Teumulong: Journal of Community Service, 2025)
The community service activity conducted at SMAS Santu Kalus Werang, West Manggarai District, East Nusa Tenggara (NTT) aims to provide psychoeducation regarding mental health for both teachers and students within the school environment. The focus of this activity is to impart knowledge about mental health to students and teachers. This effort is aimed at increasing awareness and problem-solving skills regarding mental health issues among teachers and students. The methods employed in this activity include lectures, discussions, and Q&A sessions with the goal of creating a school environment that supports students and teachers in experiencing a mentally healthy atmosphere and attaining psychological well-being. Thus, this psychoeducation lecture activity on mental health serves as an initial and concrete step towards realizing the vision and mission of Education as well as contributing to the goal of a mentally and physically healthy Indonesia.